High-dose therapy with peripheral blood progenitor cell support in patients with non-hodgkin's lymphoma - Haas, Rainer; Murea, Simona; Goldschmidt, Hartmut; Döhner, Hartmut; Moos, Marion; Witt, Barbara; Hunstein, Werner; Engenhart, Rita; Wannenmacher, Michael (Stem cells, 1995)
Between September 1991 and April 1995, high-dose therapy with peripheral blood progenitor cell (PBPC) support was administered to 105 patients with non-Hodgkin's lymphoma (NHL). Thirty-three patients had high-grade NHL, while 72 patients had different forms of low- or intermediate-grade NHL. Except for three patients who received G-CSF during steady-state hematopoiesis, PBPCs were collected following cytokine-supported cytotoxic chemotherapy. This included G-CSF or the sequential administration of interleukin 3 (IL-3) and GM-CSF. Assessing bone marrow (BM) samples before the start of chemotherapy and leukapheresis (LP) products collected during cytokine-enhanced marrow recovery, a 2.3-fold greater mean concentration of CD34+ cells was found in peripheral blood (p < 0.005). The blood-derived progenitor cells were enriched with a particular subset of more primitive progenitors, as the mean proportion of CD34+Thy-1+ cells in LP products was three-fold greater in comparison to premobilization BM samples, respectively (p < 0.001). In contrast, the mean proportion of CD34+/CD19+ and CD19+ cells in LP products was 8.8- and 80-fold smaller compared to BM samples, respectively (p < 0.001). Following high-dose conditioning therapy including TBI in 74 patients, reinfusion of PBPC resulted in rapid and sustained engraftment in the majority of patients, while in seven patients an unsubstituted platelet count of greater than 20 x 109/1 was reached between 31 and 51 days. Five patients died of treatment-related complications between 13 and 188 days following transplantation. The probability of long-term disease-free survival at 30 months in patients autografted while they were in first remission was 70% in high-grade and 83% in low-grade NHL, respectively. The data may provide the rationale for the use of PBPC-supported high-dose regimens as first-line treatment for patients at high risk of treatment failure.